2011
DOI: 10.1590/s0004-28032011000100014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-glutamine supplementation on the myenteric neurons from the duodenum and cecum of diabetic rats

Abstract: -Context -Peripheral neuropathy is one of the chronic complications of diabetes mellitus and is directly related to gastrointestinal consequences of the disease. Myenteric neurons are affected in some pathological conditions such as diabetic neuropathy.The imbalance between cellular antioxidants and free radicals, leading to an increase in oxidative stress, is considered one of the main factors responsible for neuronal damages in diabetes. Drugs that reduce the oxidative stress may play a significant role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Thus, we can infer that diabetes promoted a reduction of neuron metabolism, leading to the death of a portion of its neuronal population. We observed a reduction of more than half of these neurons, and diabetic neuropathy was observed, similar to studies that used other experimental models of diabetes and evaluated different regions of the gastrointestinal tract, including the stomach (Takahashi et al 1997;Fregonesi et al 2001), duodenum (Pereira et al 2006;Zanoni et al 2011;Lopes et al 2012), jejunum (Defani et al 2003;De Freitas et al 2008;Alves et al 2010;HermesUliana et al 2014), ileum Shotton and Lincoln 2006;Pereira et al 2011), cecum (Zanoni et al 1997;Zanoni et al 2011), and proximal colon (Tashima et al 2007;Roldi et al 2009). The development of neuropathy affects different types of enteric neurons, which are responsible for the control of important functions, such as motility, secretion, blood flow, and growth aspects of the local mucosal immune system (Furness 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, we can infer that diabetes promoted a reduction of neuron metabolism, leading to the death of a portion of its neuronal population. We observed a reduction of more than half of these neurons, and diabetic neuropathy was observed, similar to studies that used other experimental models of diabetes and evaluated different regions of the gastrointestinal tract, including the stomach (Takahashi et al 1997;Fregonesi et al 2001), duodenum (Pereira et al 2006;Zanoni et al 2011;Lopes et al 2012), jejunum (Defani et al 2003;De Freitas et al 2008;Alves et al 2010;HermesUliana et al 2014), ileum Shotton and Lincoln 2006;Pereira et al 2011), cecum (Zanoni et al 1997;Zanoni et al 2011), and proximal colon (Tashima et al 2007;Roldi et al 2009). The development of neuropathy affects different types of enteric neurons, which are responsible for the control of important functions, such as motility, secretion, blood flow, and growth aspects of the local mucosal immune system (Furness 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Among the chronic complications caused by diabetes, neurological manifestations are the most common, affecting both the autonomic and peripheral nervous systems and impairing the quality of life of patients (Chandrasekharan et al 2011). Our research group found that diabetes mellitus reduced the density of myenteric neurons and enteric neural plasticity in various segments of the digestive system (Takahashi et al 1997;Zanoni et al 1997;Fregonesi et al 2001;Defani et al 2003;Zanoni et al 2003;Pereira et al 2006;Tashima et al 2007;Zanoni et al 2007;De Freitas et al 2008;Roldi et al 2009;Alves et al 2010;Pereira et al 2011;Zanoni et al 2011;Lopes et al 2012;Hermes-Uliana et al 2014). These changes in enteric innervation that arise from diabetes are attributable to persistent hyperglycemia that produces numerous metabolic changes.…”
Section: Introductionmentioning
confidence: 77%
“…Oxidative stress Kashyap et al [90] Human, mouse, rat Stomach Gastroparesis Tang et al [97] Human Duodenum, cecum Loss of enteric neurons Zanoni et al [156] Rat ICCs: Interstitial cells of Cajal; NO: Nitric oxide; nNOS: Neuronal nitric oxide synthase; GFAP: Glial fibrillary acidic protein.…”
Section: Motility Disorders In Diabetesmentioning
confidence: 99%
“…Several authors have shown that autonomic neuropathy caused chronically by diabetes mellitus is related to quantitative and morphometric changes in the enteric neurons in various GI segments [22,77,155,156] . However, studies on the number and area of glial cells in diabetes mellitus are scarce.…”
Section: Enteric Gliamentioning
confidence: 99%
“…In agreement with these results, supplementation with glutamine has been shown to reduce the loss of neurons in the duodenum of diabetic rats. This effect was attributed to the neuroprotective effect of glutamine which prevents oxidative stress by increasing the availability of reduced glutathione from glutamine (Zanoni et al, 2011).…”
Section: Resultsmentioning
confidence: 99%